The Electron Paramagnetic Resonance in the Study of Tissues Specimens - Stefaniuk, Ireneusz; Wróbel, Dagmara; Skręt, Andrzej; Skręt-Magierło, Joanna; Góra, Tomasz; Szczerba, Piotr (Current Topics in Biophysics, 2015)
The Electron Paramagnetic Spectroscopy (EPR) is the most direct and powerful method for the detection and identification of free radicals and other species with unpaired electrons. Statistics disorders are a common gynaecological disorder occurring in women. The condition afflicts around 15% of women to the extent of impairing the quality of living. According to scientific reports as many as 50% of women experiencing problems related to genital statistics disorders. The aim of this work was to investigate tissue taken from women with genital statistics disorders using the Electron Paramagnetic Resonance method. The studies on the tissue of women is one of the first studies in this area. In this work we observed a close relationship between the observed EPR signal and the consumption of omega 3 acids.